Growth and quality of mangosteen seedlings (Garcinia mangostana L.) in response to the application of humic acids - Gomes Júnior,Gedeon Almeida (2019)
Abstract The time of formation of mangosteen seedlings propagated by seeds can be considered as the biggest difficulty in the seedling production system of this species. Considering that the use of humic acids as a growth promoter has been well documented in some species, the objective of this work was to evaluate the growth of mangosteen seedlings in response to the application of humic acid (HA) doses extracted from vermicompost (0; 2; 20; 40; 200 mg C L-1). Growth rate was determined using the following variables: stem diameter, plant height, number of leaves, leaf area, stem dry matter, leaf dry matter, shoot dry matter, root dry matter, total dry matter and Dickson quality index . The dose 150 mg C L-1 was the one that approached the maximum values and therefore should be recommended for the production of seedlings. The results at 240 days after planting (DAP) showed that the HA increased the growth of mangosteen seedlings, helping to reduce the time of seedling formation under conditions for permanent planting.